2016
DOI: 10.1001/jamasurg.2016.0789
|View full text |Cite
|
Sign up to set email alerts
|

Association of Model for End-Stage Liver Disease Score With Mortality in Emergency General Surgery Patients

Abstract: In this study, MELD score was associated with 90-day mortality following EGS in patients with CLD. The MELD score can be used as a prognostic factor in this patient population and should be used in preoperative risk prediction models and when counseling EGS patients on the risks and benefits of operative intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…However, because most major complications occurring in cirrhotic patients do require in‐patient admission, we feel that this study is reflective of the general population. We also noted that the admission MELD score for our population is lower than expected compared to other academic medical centres, 36,37 possibly limiting the generalisability of our results. However, this may also reflect the benefits of NSBBs in patients in less advanced stages of cirrhosis.…”
Section: Discussioncontrasting
confidence: 67%
“…However, because most major complications occurring in cirrhotic patients do require in‐patient admission, we feel that this study is reflective of the general population. We also noted that the admission MELD score for our population is lower than expected compared to other academic medical centres, 36,37 possibly limiting the generalisability of our results. However, this may also reflect the benefits of NSBBs in patients in less advanced stages of cirrhosis.…”
Section: Discussioncontrasting
confidence: 67%
“…In concordance with our findings, Hemida et al [29] showed that the MELD score had high sensitivity (100%) and moderate specificity (64%) for the prediction of death in cirrhotic cases submitted to non-hepatic procedures. Another retrospective study demonstrated that MELD score was associated with 90-day mortality following emergency surgery in patients with cirrhosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have used markers such as MELD and Child-Pugh scoring to predict operative outcomes in cirrhotic patients [ 9 - 11 ]. MELD was originally created to predict 30-day mortality after a TIPS procedure in a liver transplant candidate but has become a marker for severity of liver disease and is currently used to prioritize patients on the transplant list [ 12 ].…”
Section: Discussionmentioning
confidence: 99%